MADS-box transcription factors determine the duration of temporary winter dormancy in closely related evergreen and deciduous Iris spp. (8th November 2021) - Li, Danqing; Shao, Lingmei; Zhang, Jiao; Wang, Xiaobin; Zhang, Dong; Horvath, David P; Zhang, Liangsheng; Zhang, Jiaping; Xia, Yiping
Abstract: Winter dormancy (WD) is a crucial strategy for plants coping with potentially deadly environments. In recent decades, this process has been extensively studied in economically important perennial eudicots due to changing climate. However, in evergreen monocots with no chilling requirements, dormancy processes are so far a mystery. In this study, we compared the WD process in closely related evergreen ( Iris japonica ) and deciduous ( I. tectorum ) iris species across crucial developmental time points. Both iris species exhibit a 'temporary' WD process with distinct durations, and could easily resume growth under warm conditions. To decipher transcriptional changes, full-length sequencing for evergreen iris and short read RNA sequencing for deciduous iris were applied to generate respective reference transcriptomes. Combining results from a multipronged approach, SHORT VEGETATIVE PHASE and FRUITFULL ( FUL ) from MADS-box was associated with a dormancy- and a growth-related module, respectively. They were co-expressed with genes involved in phytohormone signaling, carbohydrate metabolism, and environmental adaptation. Also, gene expression patterns and physiological changes in the above pathways highlighted potential abscisic acid and jasmonic acid antagonism in coordinating growth and stress responses, whereas differences in carbohydrate metabolism and reactive oxygen species scavenging might lead to species-specific WD durations. Moreover, a detailed analysis of MIKC C MADS-box in irises revealed common features described in eudicots as well as possible new roles for monocots during temporary WD, such as FLOWERING LOCUS C and FUL . In essence, our results not only provide a portrait of temporary WD in perennial monocots but also offer new insights into the regulatory mechanism underlying WD in plants. Abstract : Evergreen and deciduous irises exhibit a temporary winter dormancy process without chilling requirements but distinct durations, regulated by MIKC C MADS-box transcription factors with common features in eudicots and new roles in monocots.